Vortex-interface interactions in two-dimensional flows. (October 2021) - Fuster, Daniel; Rossi, Maurice
Abstract: This work focuses on the basic interactions between a vortex and an interface separating two incompressible fluids. Specifically, we investigate how vorticity produced at an interface influences the dynamics of this very same interface and how the produced vorticity engenders small scales and small droplets. A critical Weber number W e c ( 1 ) exists discriminating the conditions upon which the interface rolls up around the vortex significantly. In addition, we show that a second critical Weber number W e c ( 2 ) appears. For Weber numbers below this value, the dynamic response of the interface only depends slightly on the Reynolds number. For Weber numbers above W e c ( 2 ), the vorticity layers generated by the interface itself trigger a combined Rayleigh–Taylor and Kelvin–Helmholtz instability that leads to the appearance of extremely small structures with a characteristic size that strongly depends on the Reynolds number. Highlights: We show how vorticity produced at an interface influences the dynamics of this very same interface. We show how the produced vorticity engenders small scales and small droplets. A critical Weber number discriminates the conditions upon which the interface rolls up around the vortex. A second critical Weber appears depending on whether the response significantly depends on the Reynolds number or not.